Gulf Coast Lupine, Lupinus westianus var. westianus - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Gulf coast lupine (Lupinus westianus var. westianus) is listed as threatened by the Plants in the Preservation of Native Flora of Florida Act, Chapter 5B-40, Florida Administrative Code, 1998, amended (Wunderlin et al. 2017). The species is endemic to coastal counties in the western Panhandle of Florida. Two disjunct populations are noted with Lupinus westianus var. aridorum occurring only in the central peninsula of Florida. Gulf coast lupine occurs in beach dunes, coastal grasslands, coastal scrub, sandhills, and disturbed areas such as roadsides. Gulf coast lupine can be distinguished from a similar lupine (L. diffusus) by the lack of a petiole. Several pollinators are sustained by gulf coast lupine, and the inflorescences are remarkably showy. Lupines form symbiotic relationships with nitrogen-fixing microorganisms within the soil (Gutiérrez Mañero et al. 2003). https://edis.ifas.ufl.edu/sg175